The judge - Colt, Peter, 1973- (Colt, Peter, 1973- Andy Roark mysteries, 2024)
"Boston, 1985. With the late December cold comes a new job for ex-military operative turned private investigator Andy Roark. Boston judge Ambrose Messer is being blackmailed, and he needs Roark's help to stop the culprit. Messer is judging the bench trial of a chemical company accused of knowingly dumping chemical waste in an unsafe manner, causing birth defects and cancer. The evidence against them is overwhelming, but the message from the blackmailer is clear: If you don't want the world to know your secret, the chemical company wins. Messer doesn't want to let a threat corrupt his judgement . . . but then again, he could lose everything if his secret comes out! Judging his client to be a man with morals, Roark plunges into action, determined to find the blackmailer before it's too late. But the disturbing, unexpected revelations he uncovers make him a target of some very dangerous people, who soon seem determined not only to wreck the life of his client, but to destroy Roark's too . . ." --